Implementasi Diagnosa Penyakit Pada Tanaman Anggur Menggunakan Metode CBR (Case Based Reasoning) Berbasis Website - Iskandar Dinata; Sofa Sofiana (CV. Multi Kreasi Media, 2022)
The number of diseases that occur in grapevines today can make farmers overwhelmed in determining the solution that will be made in handling each case that occurs. The Azura Grape Garden is a relatively new place for grape cultivators, so the knowledge of an expert is still needed to support the productivity of the grapevine itself. considering the disease that occurs, it is necessary to handle it quickly and precisely in the process of diagnosing the disease itself, so we need an expert system that is able to assist / manage in solving the problems of existing farmers. The case-based reasoning method used in the system is based on every symptom and disease that occurs often, so in this case a comparison method is needed between new cases so that the resulting results can be more accurate, besides that in the calculation process a method is needed in determining a finding that occurs so that the closest neighbor similarity method is used in this study.